2016
DOI: 10.1093/mnras/stw1293
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain and spectral properties of pulsars at 154 MHz

Abstract: We present 154 MHz Murchison Widefield Array imaging observations and variability information for a sample of pulsars. Over the declination range −80• < δ < 10• we detect 17 known pulsars with mean flux density greater than 0.3 Jy. We explore the variability properties of this sample on timescales of minutes to years. For three of these pulsars, PSR J0953+0755, PSR J0437−4715 and PSR J0630−2834 we observe interstellar scintillation and variability on timescales of greater than 2 minutes. One further pulsar, PS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 76 publications
3
30
0
Order By: Relevance
“…Once corrected for observational selection effects, the intrinsic average pulsar slope is α = −1.4±1.0 (Bates, Lorimer & Verbiest 2013). These values are in line with recent samples selected at low frequencies (∼ 100 − 200 MHz; Bilous et al 2016;Frail et al 2016;Bell et al 2016;Murphy et al 2017b). Polarisation can be another useful discriminant since pulsar profiles are often strongly polarised in linear and circular polarisation (Han et al 2009).…”
Section: An Excess Of Steep-spectrum Sources On the Galactic Planesupporting
confidence: 91%
“…Once corrected for observational selection effects, the intrinsic average pulsar slope is α = −1.4±1.0 (Bates, Lorimer & Verbiest 2013). These values are in line with recent samples selected at low frequencies (∼ 100 − 200 MHz; Bilous et al 2016;Frail et al 2016;Bell et al 2016;Murphy et al 2017b). Polarisation can be another useful discriminant since pulsar profiles are often strongly polarised in linear and circular polarisation (Han et al 2009).…”
Section: An Excess Of Steep-spectrum Sources On the Galactic Planesupporting
confidence: 91%
“…We refer the reader to Noutsos et al (2015) for further discussion of the physics behind the broad-band polarisation properties of pulsars. Previous observations with the MWA at 154 MHz found evidence of scintillation (Bell et al, 2016). However, this would not typically affect the fractional polarisation.…”
Section: Gleam J063049−283438mentioning
confidence: 81%
“…The pulsar has also been detected as an MWA continuum source in GLEAM data by Murphy et al (2017a), who measured a flux density of 292 ± 14 mJy at 200 MHz, and appears in the GLEAM extragalactic catalogue as GLEAM J003408-072153. Bell et al (2016) found that this pulsar was a variable continuum source at 154 MHz and concluded that refractive scintillation was the most plausible cause of the variability they observed.…”
Section: The Pulsar Psr J0034-0721 and Pulsar Searchingmentioning
confidence: 93%